Cardiovascular findings in classic homocystinuria - Marco Antônio Baptista Kalil; Karina Carvalho Donis; Fabiano de Oliveira Poswar; Bruna Bento dos Santos; Ângela Barreto Santiago Santos; Ida Vanessa Doederlein Schwartz (Molecular Genetics and Metabolism Reports, 2020)
Objective: describe cardiovascular findings from echocardiograms and electrocardiograms in patients with Classic Homocystinuria Methods: this retrospective exploratory study evaluated fourteen subjects with Classic Homocystinuria (median age = 27.3 years; male n = 8, B6-non-responsive n = 9 patients), recruited by convenience sampling from patients seen Hospital de Clínicas de Porto Alegre (Brazil), between January 1997 and July 2020. Data on clinical findings, echocardiogram and electrocardiogram were retrieved from medical records. Results: Eight patients presented some abnormalities on echocardiogram (n = 6) or electrocardiogram (n = 5). The most frequent finding was mild tricuspid regurgitation (n = 3), followed by mitral valve prolapse, mild mitral regurgitation, enlarged left atrium and aortic valve sclerosis (n = 2 patients each). Aortic root ectasia was found in one patient. Venous thrombosis was reported in six patients: deep vein thrombosis of lower limbs (n = 3), ischaemic stroke (n = 1), cerebral venous sinus thrombosis (n = 1) and pulmonary vein thrombosis (n = 1). Conclusion: mild valvulopathies seen to be common in patients with Classic Homocystinuria, but more studies regarding echocardiogram and electrocardiogram in this population are needed to draw absolute conclusions.